The Influence of Team Work And Training on The Performance of Preparation Division Employees at PT Adis Dimension Footwear,Tangerang Regency - May, Siti Kartika; Fahmi, Khaerul; Setiawan, Temmy (UJoST- Universal Journal of Science and Technology, 2026)
This study aims to determine: (1) the partial effect of teamwork on employee performance; (2) the partial effect of training on employee performance; (3) the simultaneous effect of teamwork and training on employee performance.This study uses a quantitative descriptive method, which describes variables as they are, supported by numerical data generated from actual conditions. The population in this study was all employees in the Preparation department at PT. Adis Dimension Footwear Balaraja-Tangerang. The research sample consisted of 50 respondents. This study used a saturated sampling technique due to the small population size; therefore, the sample in this study used the entire population of 50 employees as respondents. Data collection techniques used were observation, questionnaires, and documentation. Data analysis used multiple linear regression analysis using SPSS 26. Data validity was obtained through a partial t-test and a simultaneous F-test.